NEW DOMINANT ECONOMIC LOGIC AND ITS IMPACT ON EUROPEAN LEVEL. AN ECONOMETRIC APPROACH - Isabella-Cristiana, SIMA; Camelia-Aurelia, MARIN (Strategii Manageriale, 2013)
The world is changing; a new dominant economic logic appears. What we can see now is that this change doesn’t seem to come from economic leaders, it comes from emergent economies like BRICS Group or the “4 Asian Tigers”. The European Union economic links with those groups are more and more obvious, so this thesis wants to be an analysis of how those dominant logical changes influence the European Union economy. In this way, we made an analysis of statistic dates and an econometric analysis using multiple regressions.